Poly-Ether-Ether-Ketone (PEEK) in orthopaedic practice- A current concept review - Makena Mbogori; Abhishek Vaish; Raju Vaishya; Abid Haleem; Mohd Javaid (Journal of Orthopaedic Reports, 2022)
Background- Poly-Ether-Ether-Ketone (PEEK) is among the newer special thermoplastic engineering plastics and has shown reasonable biological, mechanical, and chemical properties as a biomaterial in orthopaedics. Objectives- We did an extensive and up to date review on PEEK material in orthopaedics on various search engines e.g. PUBMED, SCOPUS, Google Scholar etc. The relevant details of literature search are presented in this review article.ContentsCompared to traditional biomaterials such as metals, PEEK has the advantage of less stress shielding, is lightweight, avoids adverse reactions caused by metallic ions, compatible with computer tomography and magnetic resonance imaging techniques, and maintains high performance with most sterilization techniques. The ideal modulus of elasticity of PEEK is closer to that of bone; thus, the joint can bear weight and move like bone. PEEK is lighter than metals, allowing patients to move about more freely. PEEK can be used with other materials such as carbon fibre to improve bone tissue performance. These applications include fracture fixation implants, arthroplasty implants, bearing surfaces, spinal fusion cages, arthroscopic devices such as suture anchors and interference screws, and 3-D printing of patient-specific implants for osteotomies. Several recent studies have reported similar or slightly better clinical outcomes for PEEK implants than metals and other polymers such as Ultra High Molecular Weight Poly-Ethelene (UHMWPE). The main drawback of PEEK as a biomaterial is the complexity and high cost of manufacturing and lack of thermoformability. PEEK, however, as a biomaterial, is a very viable option for a large variety of orthopaedic applications with several advantages over the traditional biomaterials. High-quality application-based studies on short- and long-term clinical and functional outcomes are required.